2016
DOI: 10.1111/obr.12423
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of commercial weight loss programmes’ effect on glycemic outcomes among overweight and obese adults with and without type 2 diabetes mellitus

Abstract: Objective We examined the glycemic benefits of commercial weight-loss programs as compared to control/education or counseling among overweight and obese adults who had or who were at increased risk for type 2 diabetes mellitus (T2DM). Methods We searched MEDLINE, Cochrane Database of Systematic Reviews, and references cited by individual programs. We included randomized controlled trials (RCTs) of ≥12 weeks duration. Two reviewers extracted information on study design, population characteristics, interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Mediterranean-style, DASH, and plant-based diets, sometimes with prescribed energy restriction, are recommended, but effectiveness data are limited [ 7 ] and low fat diets have not been shown to be superior for weight loss [ 10 ]. Commercially available weight loss programs have demonstrated short-term success in glycemic control, but continued success at 1 year is uncommon [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mediterranean-style, DASH, and plant-based diets, sometimes with prescribed energy restriction, are recommended, but effectiveness data are limited [ 7 ] and low fat diets have not been shown to be superior for weight loss [ 10 ]. Commercially available weight loss programs have demonstrated short-term success in glycemic control, but continued success at 1 year is uncommon [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 summarizes outcomes with Weight Watchers, Jenny Craig, and Nutrisystem, which typically comprise the majority market share in the commercial weight loss industry ( 31 , 36 41 ). Both Weight Watchers and Jenny Craig have had randomized, controlled trials (RCTs) documenting their long-term weight loss efficacy, and Jenny Craig has demonstrated long-term glycemic benefits among patients with diabetes ( 3 , 42 44 ).…”
Section: Approaching the Weight Loss Discussionmentioning
confidence: 99%
“…Our outcomes included mean change in the following: systolic blood pressure (SBP), diastolic blood pressure (DBP), LDL-c, HDL-c, triglycerides, and total cholesterol. These CVD risk factors were pre-specified secondary outcomes of our review, and we have previously reported programs’ effect on our primary outcomes of weight loss, adherence, and harms (20), and another reports glycemic outcomes (22). …”
Section: Methodsmentioning
confidence: 99%